2022
DOI: 10.3390/cancers14040902
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights on the Use of L-Asparaginase as an Efficient and Safe Anti-Cancer Therapy

Abstract: L-Asparaginase (L-ASNase) is an enzyme that hydrolyses the amino acid asparagine into aspartic acid and ammonia. Systemic administration of bacterial L-ASNase is successfully used to lower the bioavailability of this non-essential amino acid and to eradicate rapidly proliferating cancer cells with a high demand for exogenous asparagine. Currently, it is a cornerstone drug in the treatment of the most common pediatric cancer, acute lymphoblastic leukemia (ALL). Since these lymphoblasts lack the expression of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 182 publications
(228 reference statements)
0
46
0
8
Order By: Relevance
“…Unfortunately, these side effects prevent many patients from receiving their prescribed course of treatment, resulting in a detrimental impact on their outcome 50,51 . Several reports showed that the L-glutaminase co-activity of clinically used L-ASNases partially contributes to these unwanted side effects 21 . Therefore, lowering the L-glutaminase co-activity while maintaining its anti-cancer effect might provide the required safety profile that reduces treatment interruptions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, these side effects prevent many patients from receiving their prescribed course of treatment, resulting in a detrimental impact on their outcome 50,51 . Several reports showed that the L-glutaminase co-activity of clinically used L-ASNases partially contributes to these unwanted side effects 21 . Therefore, lowering the L-glutaminase co-activity while maintaining its anti-cancer effect might provide the required safety profile that reduces treatment interruptions.…”
Section: Discussionmentioning
confidence: 99%
“…Because Gln levels are much higher, extensive ammonia levels are produced which might contribute to L-ASNase induced neurotoxicity [18][19][20] . The L-glutaminase co-activity also has an impact on protein synthesis in the liver and pancreas resulting in hepatotoxicity, pancreatitis, hyperglycemia, leukopenia and thrombosis 6,14,21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Bacteroides caccae, Bifidobacterium dentium, and Blautia producta ., indicating that these bacteria used Asn as a growth source, and thus could affect Asn levels in the gut and perhaps of CRC patients. Whereas there are side effects associated with ASNase administration; E. coli ASNase can bind and inhibit the concanavalin A receptor, which accounts for non-immunological side effects and toxicities by ASNase ( Van Trimpont et al, 2022 ). Moreover, the Rhodospirillum rubrum mutant L-ASNase is unique to other bacterial ASNases as it can penetrate cancer cells via a clathrin receptor-dependent manner that suppressed telomerase activity and led to asparagine-independent cytotoxicity ( Zhdanov et al, 2017 ).…”
Section: Extracellular Sources Of Asparaginementioning
confidence: 99%
“…Only asparaginase II is used for clinical application [11], and industrialized enzyme preparations are obtained from bacteria, such as the enzyme derived from E. coli in native and pegylated forms and the enzyme derived from Dickeya chrysanthemi (syn. Erwinia chrysanthemi) [12]. However, adverse effects such as hypersensitivity, coagulation disorders, pancreatitis, hyperglycaemia, hepatotoxicity and resistance to L-asparaginase with antibody formation in children with leukemia and lymphoma as well as in adults undergoing induction treatment for ALL when E. coli and D. chrysanthemi asparaginase were administered have been reported [13].…”
Section: Introductionmentioning
confidence: 99%